How to reduce the risk of ischemic stroke? Overview of recommendations and their effectiveness - Bondos, Borys; Niewiadomska, Jagoda; Stępień, Aleksandra; Paluch, Alicja; Skrzypek, Jakub; Niekra, Aleksandra; Fussek, Łukasz; Kochan, Robert; Wieczorek, Ewelina; Lee, Kacper (Journal of Education, Health and Sport, 2024)
Stroke is a very serious life-threatening condition. It is the second cause of death worldwide [5], while even in non-fatal cases it can result in severe disability and complications [5, 8]. Of all cases, ischaemic stroke is the most common, accounting for 87% of all ischaemic stroke cases [4]. Some hope is offered by the fact that modifiable risk factors are responsible for 90% of ischaemic stroke cases [7, 14]. Consequently, a number of recommendations have been made regarding health-promoting behaviours and treatment goals for diseases associated with an increased risk of stroke in high-risk populations. The aim of this work is to present risk groups, i.e. patient groups at higher than population risk of stroke, and to assess the effectiveness of the recommendations and the impact of their application on stroke risk. Methods and materials We reviewed the literature available on PubMed and Google Scholar using the words: Stroke, ischemic stroke, prevention, epidemiology Summary The data analysed clearly indicate that modifiable risk factors are responsible for the majority of cases (up to 90%) of stroke. Identifying risk groups on the basis of the Life’s Essential 8 proposed by the American Heart Association for the prevention of cardiovascular disease, yields measurable results in lowering the risk of stroke among patients. Clearly defined standards can also set therapeutic targets for the treatment of conditions and diseases strongly associated with stroke risk and further improve population health. Primary care plays a very important role, as it is often the patient’s first contact with the health care system. Keywords: Stroke, ischemic stroke, prevention, epidemiology